The Development of Edutourism Research : A Bibliometric Analysis - Bhakti , Aditya Dwi Putra; Prakoso , Havidz Ageng; Nasvian , Moch. Fuad; Bakhtiar, Ary; Wibowo , Novin Farid Styo; Anwar , Vivi Alayda (Journal of Ecohumanism, 2024)
This study delves into the development of edutourism during the 20th century, aiming to provide a comprehensive understanding of its evolution throughout the century. The primary objective of this research is to examine the growth of edutourism and identify existing gaps in the literature to guide future studies in this field. Utilizing a bibliometric approach, we analyzed a wide range of scientific publications on edutourism, which were obtained from multiple academic databases. By employing advanced visualization techniques, we were able to identify key trends and patterns that have emerged over time. The analysis highlights a notable increase in the integration of educational and tourism components, particularly in areas like environmental education. However, despite this growth, several aspects of edutourism remain under-researched and warrant further exploration. The findings of this study underline the significant potential of edutourism within the broader context of sustainable tourism, offering critical insights for both researchers and practitioners interested in deepening their understanding of this dynamic field.